1982
DOI: 10.1002/joc.3370020206
|View full text |Cite
|
Sign up to set email alerts
|

Zonal index and circulation change in the north Atlantic area, 1873–1972

Abstract: Monthly and annual values are calculated of a zonal index based on surface pressure at 35"N and 55"N between 60"W and 1O"W. The period under study, 1873-1972, is divided into three sub-periods which approximate with three epochs proposed by Lamb (1972). A comparison of our indices with Lamb's results is followed by a discussion of our monthly index, and the rarity of easterly flow in the 100-year period is noted. The results are subjected to a trend and a power spectrum analysis and the latter indicates a numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 4 publications
2
15
0
1
Order By: Relevance
“…Our results for the Atlantic agree with what Makrogiannis et al (1982) found when they studied long term variations of the tonal index over the North Atlantic. They used mean monthly sea-level pressure data and computed mean values along 350N (SLP35) and 550N (SLP55) for an area bounded by the longitudes 600W and 100W, to define a local tonal index: SLP35-SLP55.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 92%
See 1 more Smart Citation
“…Our results for the Atlantic agree with what Makrogiannis et al (1982) found when they studied long term variations of the tonal index over the North Atlantic. They used mean monthly sea-level pressure data and computed mean values along 350N (SLP35) and 550N (SLP55) for an area bounded by the longitudes 600W and 100W, to define a local tonal index: SLP35-SLP55.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 92%
“…There are a few studies of circulation changes based on observations from the North Atlantic and Europe (Makrogiannis et al, 1982;Bardossy and Caspary, 1990). However, the first one deals with long term variations of a zonal index, and the frequency of low index situations is not the same as frequency of blocked flow.…”
Section: Introductionmentioning
confidence: 99%
“…The inverse relationship (high index-low precipitation and 6ice 6ersa) is also found in the other PC series, which is less clear due mainly to the influence of easterly patterns for the Mediterranean Coast and the influence of the mountains for the Cantabric area. Another way to compute the zonal index is to take the difference in pressure between 35 and 55°N (Makrogiannis et al, 1982;Makrogiannis, 1983). The inverse relationship is clearer with this index for the 1st annual PC series, except during the 1930s (relatively high index-high precipitation) and the 1950s (relatively low index-low precipitation).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies (Parker et al, 1994;Hurrell et al, 2003Hurrell et al, ) described 1901Hurrell et al, -1930 as a period of increased westerly winds and cyclonicity over the mid-latitude North Atlantic. Strong zonal circulation during 1920-1930 was identified by Makrogiannis et al (1982). The 1920s was a period of increased cyclone activity in the North Atlantic with the exception of some increase in blocking activity around 1920 (Slonosky et al, 2000).…”
Section: Discussionmentioning
confidence: 99%